To solve the equation, we will start by distributing -2 to (-c - 20):
-2(-c - 20) = -2c - 20
2c + 40 = -2c - 20
Now, we will combine like terms:
2c + 40 + 2c = -2c - 20 + 2c
4c + 40 = -20
Next, we will isolate the variable terms:
4c + 40 - 40 = -20 - 40
4c = -60
Finally, we will solve for c by dividing both sides of the equation by 4:
4c/4 = -60/4
c = -15
Therefore, the solution to the equation is c = -15.
The correct choice is:
A. c = -15
Solve the equation. Note if the equation is an identity or if it has no solution.
-2(-c - 20) = -2c - 20
Part 1
Select the correct choice and fill in any answer boxes in your choice below.
A.
c =
B.
The equation is an identity.
C.
The equation has no solution.
1 answer